Символіка залізних виробів у захисних обрядах від грози в традиційній культурі українців - Тупчієнко, М. (Народна творчість та етнографія, 2008)
The article is an attempt to investigate the mechanism of origin and functioning of the symbolic meanings of ironworks which were used by the Ukrainians in the rites of protection from thunderstorm.